Petrological and geochemical characteristics of xylites and associated lipids from the First Lusatian lignite seam (Konin Basin, Poland): Implications for floral sources, decomposition and environmental conditions. (September 2020) - Bechtel, Achim; Widera, Marek; Lücke, Andreas; Groß, Doris; Woszczyk, Michał
Highlights: Xylites are affected by weak gelification and advanced cellulose decomposition. δ 13 C of xylites reflect the extent of cellulose decomposition. Xylites represent wood remains of the same species of conifers in the lignite. Fluctuating δ 13 C and δ 2 H of lipids within the seam are caused by water availability. Abstract: Single pieces of fossil wood fragments (xylites) were collected from the middle Miocene First Lusatian lignite seam at the Adamów, Jóźwin IIB and Tomisławice opencast mines and are characterized by maceral variety, cellulose contents and their molecular and isotopic composition. Biomarker composition of xylites and δ 13 C of their total organic matter, lipids and cellulose are used to provide insights into woody plant community and the effects of wood decomposition. The investigated xylites represent fragments of fossil wood from conifers, most likely species of Cupressaceae, indicated by terpenoid biomarkers characteristic for conifers and by the δ 13 C values of the extracted cellulose. This conclusion is confirmed by paleobotanical data highlighting Taxodium and Nyssa as the main elements of the wet forest swamps. Due to the wet swamp habitat and the higher-decay resistance exclusively wood fragments of conifers are found in the lignite seam. Minor abundances of angiosperm-derived triterpenoids in the xylites are explained by impurities from inherent detritic lignite. The xylites are characterized by minor to moderate extents of gelification, but elevated to high cellulose decomposition. The relationship between δ 13 C values of xylites and their cellulose contents reflects wood decomposition removing preferentially the 13 C-enriched compounds, but decomposition did not affect the δ 13 C of cellulose. Despite of similar δ 13 C of xylites and detritic lignite, differences in isotopic composition of hopanoids argue for slightly different microbial communities involved in the decomposition of the respective OM. Thus, we conclude that wood decomposition proceeded in a freshwater environment under acidic conditions by fungi and bacteria. Variations in water availability during growth periods of the conifers are suggested as the most probable cause for the observed minor variations in isotopic composition of plant lipids. The positive relationship found between δ 2 H and δ 13 C of plant biomarkers, and cellulose of xylites can be explained by the ability of vascular plants to minimize evapotranspiration during dryer phases resulting in plant OM enriched in 13 C and 2 H. The significant differences in δ 2 H between diterpenoids of different structural types and n -alkanes are most likely caused by differences in isotopic fractionation during lipid biosynthesis.